Financial impacts of smart meter security and privacy breach - Yussof S.; Rusli M.E.; Yusoff Y.; Ismail R.; Ghapar A.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Data privacy; Electric power transmission; Electric power transmission networks; Electric utilities; Energy utilization; Finance; Losses; Mobile security; Smart meters; Financial impacts; Information and Communication Technologies; Privacy breaches; security; Security and privacy; Security Economics; Security policy; Utility companies; Smart power grids